Development of mobile application for event management system - Razali, Muhammad Imran Hakimi; Arifin, Noorfadzilah; Ahmad, Marina; Manaf, Maznie (International Journal of Accounting, Finance and Business, 2024)
Currently, mobile applications play a pivotal role in shaping the campus life experience. Existing event management mobile applications serve as versatile tools that seamlessly integrate technology into various aspects of academic and social activities. Therefore, the objective of this study is to develop a mobile application known as The EventHub: UiTM Machang Application that will make easier for the UiTM Machang campus community to keep track of upcoming events and manage them effectively. This study was motivated by the challenges to check all upcoming events since all related information was scattered. Besides that, there was no systematic way to track participant registration lists and participant attendance lists since the organizers kept track of both lists using paper and simple spreadsheets. Hence, the development of The Eventhub: UiTM Machang Application enables the UiTM Machang campus community to easily monitor all upcoming events, thereby enhancing the effectiveness of managing campus events. The Eventhub: UiTM Machang Application was developed using the Mobile Application Development Life Cycle (MADLC). As a result, this study developed interfaces for organizers, which are to create and manage events, create QR codes, track registered participants, track attendance lists, and track feedback. While interfaces for participants are to register events, record attendance by scanning the organizer's QR code during the event, submit feedback and admin interfaces are to track events and registered participants, track attendance lists and generate reports. Implicitly, The Eventhub: UiTM Machang Application contributes to increase productivity among the UiTM Machang campus community.